Unveiling the surface dominated capacitive properties in flexible ternary polyaniline/NiFe2O4/reduced graphene oxide nanocomposites hydrogel electrode for supercapacitor applications. (1st December 2022) - Sardana, Silki; Aggarwal, Kanika; Malik, Sanket; Saini, Ayushi; Dahiya, Sajjan; Punia, Rajesh; Maan, A.S.; Singh, Kuldeep; Ohlan, Anil
Highlights: 3D ternary polyaniline/NiFe2 O4 /rGO (PNFG) hydrogels on carbon cloth were synthesized. PNFG on carbon cloth act as binder-free flexible electrodes for supercapacitors. Maximum specific capacitance of 1134.28 F/g at a current density of 1 A/g. The symmetric supercapacitor cell delivered Es of 19.29 Wh/kg and Ps of 0.61 kW/kg. Performance depends on surface-controlled and diffusion-controlled mechanism. Abstract: The 3D ternary nanocomposites hydrogel have been effectively fabricated on carbon cloth using a two-step synthesis approach. Nickel ferrite nanoparticles (NiFe2 O4 ) prepared by template method have been dispersed onto/within rGO nanosheets leading to the formation of NiFe2 O4 /rGO (NFG) nanocomposites. Afterward, polyaniline hydrogel has been polymerized on NFG nanosheets to prepare ternary polyaniline/NiFe2 O4 /rGO hydrogel (PNFG) nanocomposites on carbon cloth that can be further utilized as a binder-free supercapacitor electrode. The resulting 3D ternary nanocomposites hydrogel achieved maximum specific capacitance of 1134.28 F/g at a current density of 1 A/g and 76.46 % of capacitive retention at 10 A/g. The supercapacitor electrode exhibited outstanding rate capability and superior cyclic stability up to 5000 successive cycles. In addition, the symmetric supercapacitor cell delivered 0.61 kW/kg of specific power and 19.29 Wh/kg of specific energy. The excellent electrochemical characteristics of PNFG is ascribed to its well-designed 3D microstructure and the synergistic effect created by the capacitive mechanism due to electric double layer capacitance (EDLC) and pseudocapacitance (surface redox reactions) as well as diffusion-controlled mechanism (faradaic redox reactions). It has been revealed that the overall electrode reaction is dominated by surface-controlled processes, with a small contribution from diffusion-controlled faradaic processes. Graphical abstract: Image, graphical abstract